Chlamydia trachomatis serovar distribution and Neisseria gonorrhoeae coinfection in male patients with urethritis in Greece. - Papadogeorgakis, Helen; Pittaras, Theodore E; Papaparaskevas, Joseph; Pitiriga, Vassiliki; Katsambas, Andreas; Tsakris, Athanassios (J Clin Microbiol, 2010)
The distribution of Chlamydia trachomatis serovars and Neisseria gonorrhoeae coinfection was studied in a group of 100 C. trachomatis-positive males with urethritis in Greece. The serovar distribution revealed that apart from the predominant worldwide types E and F, the relatively uncommon type G is also prevalent. Gonococcal coinfection was frequent (30%) and was associated with genovariant Ja (75%, P = 0.008).
Keywords: Adult; Chlamydia Infections; Chlamydia trachomatis; Comorbidity; Gonorrhea; Greece; Humans; Male; Neisseria gonorrhoeae; Serotyping; Urethritis; Young Adult